Pendidikan dalam Peningkatan Kualitas Usaha Mikro Kecil dan Menengah - Sugiono, Sugiono; Latief, Jamil; Rahmanisa, Rahmanisa (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Micro, small and medium enterprises (MSMEs) play an important role in economic growth. Education is an important part of strengthening MSMEs. This research uses qualitative methods, data collection is carried out by semi-structured interviews. The resource persons in the research are MSME owners. Analyze data with flow data analysis. The results showed that education has an important role in improving the quality of MSMEs in terms of education, aspects of business governance, aspects of marketing and aspects of financial governance